2003
DOI: 10.1590/s0074-02762003000300008
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the stridulatory sulcus, buccula and rostrum of the nymphs of Triatoma guazu Lent & Wygodzinsky, 1979 and Triatoma jurbergi Carcavallo, Galvão & Lent, 1998 by scanning electron microscopy (Hemiptera, Reduviidae)

Abstract: The ultrastructural morphology of the ventral region of the head (rostrum and buccula) and proesternum (stridulatory sulcus) of nymphs from the 1st to 5th instars of Triatoma guazu Wygodzinsky, 1979 and Triatoma jurbergi Carcavallo, Galvão & was described. Morphological differences between the two species and of the five nymphal stages development of each species were observed. These structures showed systematic differential characteristics of the studied species and may be used to increase their taxonomic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
1
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 10 publications
0
9
1
5
Order By: Relevance
“…In the present study on R. brethesi, it was found to have the shape of an amphora. In this, it differs from what has been observed for other genera, and for other species of the same genus, as demonstrated by Lent and Wygodzinsky (1979) and Silva et al (2003).…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…In the present study on R. brethesi, it was found to have the shape of an amphora. In this, it differs from what has been observed for other genera, and for other species of the same genus, as demonstrated by Lent and Wygodzinsky (1979) and Silva et al (2003).…”
Section: Discussioncontrasting
confidence: 83%
“…In this, it differs from the species Triatoma williami and Triatoma gerstaeckeri (Ferro et al 1997) and also from Triatoma guazu and Triatoma jurbergi (Silva et al 2003), which have a U-shaped format.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In the present study this structure was useful to distinguish T. williami and T. klugi, from T. vandae. Silva (1999Silva ( , 2000 and Silva et al (2003) analysed the buccula of T. guazu and T. jubergi at all nymphal stages and concluded that this structure differed between both species, being suggested as an additional taxonomic trait. Catalá (1996) described ten sensillae on the rostrum of eight species of Triatomine and concluded that the chaetigerous sensillae is more abundant in the rostrum in six lines along the main axe of the 2 nd and 3 rd segments.…”
Section: Diagnosismentioning
confidence: 99%